Assessment of Personality Dimensions in Children and Adolescents with Bipolar Disorder Using the Junior Temperament and Character Inventory - Olvera, Rene L. (Mary Ann Liebert, Inc., 2009)
OBJECTIVE: We compared temperament and character traits in children and adolescents with bipolar disorder (BP) and healthy control (HC) subjects. METHOD: Sixty nine subjects (38 BP and 31 HC), 8–17 years old, were assessed with the Kiddie Schedule for Affective Disorders and Schizophrenia–Present and Lifetime. Temperament and character traits were measured with parent and child versions of the Junior Temperament and Character Inventory. RESULTS: BP subjects scored higher on novelty seeking, harm avoidance, and fantasy subscales, and lower on reward dependence, persistence, self-directedness, and cooperativeness compared to HC (all p < 0.007), by child and parent reports. These findings were consistent in both children and adolescents. Higher parent-rated novelty seeking, lower self-directedness, and lower cooperativeness were associated with co-morbid attention-deficit/hyperactivity disorder (ADHD). Lower parent-rated reward dependence was associated with co-morbid conduct disorder, and higher child-rated persistence was associated with co-morbid anxiety. CONCLUSIONS: These findings support previous reports of differences in temperament in BP children and adolescents and may assist in a greater understating of BP children and adolescents beyond mood symptomatology.